2011
DOI: 10.1152/ajpgi.00229.2010
|View full text |Cite
|
Sign up to set email alerts
|

Different functions of intestinal and liver-type fatty acid-binding proteins in intestine and in whole body energy homeostasis

Abstract: It has long been known that mammalian enterocytes coexpress two members of the fatty acid-binding protein (FABP) family, the intestinal FABP (IFABP) and the liver FABP (LFABP). Both bind long-chain fatty acids and have similar though not identical distributions in the intestinal tract. While a number of in vitro properties suggest the potential for different functions, the underlying reasons for expression of both proteins in the same cells are not known. Utilizing mice genetically lacking either IFABP or LFAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
79
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(103 citation statements)
references
References 52 publications
16
79
0
8
Order By: Relevance
“…In vertebrates, the absorption and transport of short-to medium-chain FAs occurs differently in enterocytes, as LCFAs are usually reesterifi ed inside the cell. There is evidence indicating that both FABP1 and FABP2 participate in the cellular uptake and transport of unesterifi ed FAs and the lipid metabolism ( 16,80,81 ). However, some authors report that they play a role in lipid sensing but not in direct dietary FA absorption ( 13,62,82,83 ).…”
Section: Discussionmentioning
confidence: 99%
“…In vertebrates, the absorption and transport of short-to medium-chain FAs occurs differently in enterocytes, as LCFAs are usually reesterifi ed inside the cell. There is evidence indicating that both FABP1 and FABP2 participate in the cellular uptake and transport of unesterifi ed FAs and the lipid metabolism ( 16,80,81 ). However, some authors report that they play a role in lipid sensing but not in direct dietary FA absorption ( 13,62,82,83 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our studies have demonstrated that female mice with germline deletion of L-Fabp are protected against weight gain and hepatic steatosis when fed high saturated fat (SF) diets (15)(16)(17). This phenotype cannot be attributed to increased energy metabolism or decreased absorption of dietary fat, although the kinetics of intestinal fatty acid (FA) uptake is altered in L-Fabp Ϫ / Ϫ mice ( 17,18 ). In general, L-Fabp Ϫ / Ϫ mice fed a high-fat diet exhibit a subtle (although not statistically signifi cant) decrease in average daily food consumption, a difference which would over time be suffi cient to reduce weight gain ( 15 ).…”
Section: Aged Female L-fabpmentioning
confidence: 99%
“…L-FABP, and oxidation such as PPAR␣ and PPAR␥. Furthermore, L-FABP can target fatty acids to oxidative degradation (40). Therefore, higher ␤-oxidation of FFA might be secondary to high FFA concentrations.…”
Section: Roles Of Intestinal Mtp and Abca1 In Tissue Lipidmentioning
confidence: 99%